Treatment of Naturally Occurring Periodontitis in Dogs With a New Bio-Absorbable Regenerative Matrix - Gawor, Jerzy Pawel; Strøm, Peter; Nemec, Ana (Frontiers in Veterinary Science, 2022)
Although periodontal disease is one of the most common (oral) diseases of dogs, an effective treatment approach to periodontitis lacks. The aim of this study was to evaluate safety and efficacy of a regenerative, bio-absorbable implant biomaterial made of medical grade porcine gelatin, which is crosslinked by transglutaminase into a porous scaffold for the treatment of periodontitis in dogs in a clinical setting. Nine client-owned dogs were included in this multicenter, prospective in-terventional clinical study. A split-mouth design was used to treat any teeth with periodontitis; teeth on one side of the mouth were treated with open periodontal therapy alone and teeth on the other side were treated with open periodontal therapy and the tested implant. A recheck under gen-eral anesthesia was performed three months after the initial treatment and included periodontal probing and dental radiographs and/or CBCT of the teeth included in the study. This revealed reduc-tion of the probing depth at all teeth, but in teeth treated with the implant a statistically significant improvement (average 2.1 mm) over control teeth (average 1.0 mm) was diagnosed. Similarly, al-veolar bone height was increased at most of the teeth, but in teeth treated with the implant a statis-tically significant improvement (average 1.25 mm palatally and 1.5 mm buccally) over control teeth (average 0.58 mm palatally and 0.68 mm buccally) was observed for the buccal site. Open periodontal therapy alone improves clinical parameters and alveolar bone height in dogs with peri-odontitis, which is further significantly improved by addition of the implant used.